Evidence on the link between hypothyroidism and non-alcoholic fatty liver disease: an updated systematic review - Nazanin Pourseyedi; Sara Arefhosseini; Helda Tutunchi; Mehrangiz Ebrahimi-Mameghani (BMC Endocrine Disorders)
Abstract Background Numerous studies have investigated the relationship between hypothyroidism and non-alcoholic fatty liver disease (NAFLD), while the underlying mechanisms are not well understood. This systematic review evaluated the mentioned relationship among non-diabetic adults. Methods This systematic review was written in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive literature search was conducted using PubMed, Scopus, Web of Science, and Google Scholar until January 2024. After a critical analysis, 29 observational studies were included in the present systematic review. Results The available observational evidence suggests a potential association between hypothyroidism and NAFLD. Regarding this complex relationship, patients with hypothyroidism may be more likely to develop NAFLD compared to those with normal thyroid function. Several factors are involved in the development of hypothyroidism-induced NAFLD. Conclusions Thyroid hormones regulate energy and metabolism, suggesting their relevance in NAFLD. Increased awareness and optimized strategies are needed for mutual screening and managing thyroid disease and NAFLD coexistence.